2018
DOI: 10.1161/circulationaha.118.034856
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Ambient Air Pollution and Cardiac Morpho-Functional Phenotypes

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 46 publications
3
33
0
3
Order By: Relevance
“…Altered cardiac remodelling associated with air pollution has also been recently identified in humans. In a large asymptomatic population, with no prevalent CVD, prior exposure to PM 2.5 (specific PAHs were not described) was associated with increased left and right ventricular end-diastolic volume and end-systolic volume (Aung et al 2018). A comprehensive mechanistic study by Wold et al (2012) further demonstrated that long-term (9 months) PM exposure was associated with cardiac hypertrophy, changes in cardiac myocyte phenotype and impaired cardiac contractility.…”
Section: Figure 4 Pah and Ec Coupling In Cardiac Myocytesmentioning
confidence: 99%
See 3 more Smart Citations
“…Altered cardiac remodelling associated with air pollution has also been recently identified in humans. In a large asymptomatic population, with no prevalent CVD, prior exposure to PM 2.5 (specific PAHs were not described) was associated with increased left and right ventricular end-diastolic volume and end-systolic volume (Aung et al 2018). A comprehensive mechanistic study by Wold et al (2012) further demonstrated that long-term (9 months) PM exposure was associated with cardiac hypertrophy, changes in cardiac myocyte phenotype and impaired cardiac contractility.…”
Section: Figure 4 Pah and Ec Coupling In Cardiac Myocytesmentioning
confidence: 99%
“…Similarly, a ß20% increase in stroke incidence has been observed in various European countries which met their air quality standards, indicating that current standards may not be sufficient . Concern for current air quality standards was bolstered by Aung et al (2018), who showed correlations between UK addresses, ambient air quality data (at levels within current UK air quality standards) and biventricular dilatation that is suggestive of detrimental cardiac remodelling.…”
Section: Airborne Particulate Matter and Human Health Risksmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies from Western countries have suggested that elevated ambient particulate matter <2.5 mm (PM 2.5 ) in aerodynamic diameter are consistently associated with adverse cardiovascular events or even mortality [1]. The suggested mechanism is that these events are associated with various systemic inflammatory responses after inhalation [2][3][4]. Current air quality standards in the USA and European societies are based on a 3-year average of the annual arithmetic means of PM 2.5 concentration [5,6], but clear evidence of a threshold PM 2.5 concentration associated with increased risks of cardiovascular or all-cause mortality is lacking [1,7,8].…”
Section: Introductionmentioning
confidence: 99%